Fish diversity of Lohandra River, Biratnagar, Morang, Eastern Nepal - Shrestha, Jay Narayan (Nepalese Journal of Biosciences, 2016)
Nepal has great water resources supporting diverged aquatic flora and fauna, including varieties of freshwater fishes. Lohandra river is one of the major perennial river of Morang district, eastern Nepal, originating from Mahabharat hill. Fishes of the river were collected from September, 2014 to August, 2015 using local gears and cast net with the help of local fishermen and the collected fishes were preserved in 70% alcohol facing their head downward for taxonomic identification. The present paper deals with 51 fish species belonging to 38 genera, 20 families of 7 orders. The notable ichthyofauna of the river were Clarias batracus, Garra gotyla, Botia lohachata, Chagunius chagunio, Chaca chaca, Acanthocobotis botia, Lepidocephalus guntea. Colisa faciatus, Notopterus notopterus, Cirrhinus reba, C. mrigala, Labeo dero, L. cabasu, Salmostoma bacaila, Barilius bendelisis, B. barna, Crossocheilus latius latius, Mystus species, Ompok bimaculatus, Wallago attu, Chanda nama, Nandus nandus, Anabus testudineus, Channa orientalis, C. marulius, Catla catla, Monopterus cuchia, Clupisoma garua and Psilorhyncus sucatio. As Lohandra river was rich with ichthyofauna, the investigation of ecology and fishes of the river is recommended for the conservation of these fishes.